Draft Annual Plan 1981-82 Government of Bihar - Planning Commission (Planning Commission, 1981)
The Plan In Outline, Sub-Plan, Annexure I, Annexure II, Annexure III, Annexure IV, Annexure V, Annexure VI, Annexure VII.
Government of Bihar Planning Department